Spatial audio - Rumsey, Francis (Focal Press, 2001)
Explores the principles and practical considerations of spatial sound recording and reproduction. Particular emphasis is given to the increasing importance of multichannel surround sound and 3D audio, including binaural approaches, without ignoring conventional stereo. The enhancement of spatial quality is arguably the only remaining hurdle to be overcome in pursuit of high quality sound reproduction.
Includes bibliographical references and index. - Print version record
Keywords: Sound -- Recording and reproducing; Stereophonic sound systems; Surround-sound systems; Son; Enregistrement et reproduction; Ambiophonie; TECHNOLOGY & ENGINEERING; Electrical; Sound; Recording and reproducing